Approaches for Improving Restaurant Service Quality for Lao Tourists, Nakhon Pakse, Champasak Province, the Lao People’s Democratic Repub - Sangphachan, Kikeo; Suksirisopon, Pornchai; Somnuek, Pariwat (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This study aimed to investigate 1) service processes found in restaurants among Laos’s visitors, and 2) quality evaluation of the service for the restaurants located in Pakse capital in Champasak province, Lao People's Democratic Republic. Mixed methods, consisting of quantitative and qualitative research approaches, were applied in this study with a total of 400 visitors and 10 entrepreneurs and officers of the restaurants. Survey questionnaires and Semi-structured Interviews were employed for data collection while statistics such as frequency, percentage, mean, Standard Deviation, and Content Analysis were used for data analysis. The results indicated that service processes included 1) the beginning of the service, preparation of the restaurant and surrounding areas with kitchen accessories had to be focused to create satisfactory services. 2) During the services, polite greetings had to be found while signature menus, important promotions, and drinks had to be served to the customers. 3) For after the service, the officers had to give thanks to customers and they had to remember customers’ names and inquire about service attitudes. According to the overall evaluation of the restaurant services, it was demonstrated that the customers held more expectations than perceptions concerning a concrete service and understanding of customers’ needs. Nevertheless, they held more perceptions than expectations in perspectives of confidence, responding to customers’ needs, and quality assurances. Importantly, the visitors with different ages and marital statuses held different perceptions, the statistical significance at .05.